PENERAPAN PEMBELAJARAN BERBASIS ETNOMATEMATIKA RUMAH ADAT LIMAS UNTUK MENINGKATKAN PEMAHAMAN KONSEP PENGUKURAN SUDUT KELAS V SD - Agustina, Meri; Fahriza Fuadiah, Nyiayu; Fitri Puspa Sari, Eka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by students' low level of conceptual understanding in mathematics, particularly regarding the topic of angle measurement, which tends to be abstract for elementary school students. The study aimed to enhance the mathematical conceptual understanding of fifth-grade elementary students by implementing ethnomathematics in the classroom, utilizing local wisdom values ​​derived from the Limas traditional house of Palembang. An experimental method employing a One-Group Pretest-Posttest design was used. The research subjects were fifth-grade students at SD Negeri 55 Palembang. Data collection involved a validated test designed to measure conceptual understanding of angle measurement. Data analysis was conducted using descriptive statistics, the Paired Samples T-Test, and the N-Gain Score test. The results demonstrated a significant improvement in conceptual understanding, evidenced by an increase in the mean score from 58.31 (pretest) to 83.08 (posttest). The Paired Samples T-Test yielded a significance value of 0.000 (p < 0.05), indicating that the alternative hypothesis (Ha) was accepted. The mean N-Gain index was 0.63 (moderate category), and the learning effectiveness was reflected in an N-Gain percentage of 62.61%, placing it in the